CONSEQUENCES OF SEVERE CRANIOCEREBRAL INJURY IN ADOLESCENTS: CLINICAL FEATURES AND METHODS OF TREATMENT - N.N. Zavadenko; L.S. Gudzilova; A.F. Iznak; E.V. Iznak ("Paediatrician" Publishers LLC, 2010)
Neurological and neuropsychological examination of 104 patients (58 boys and 46 girls) 12-19 years old who had closed moderate or severe craniocerebral injury (CCI) (cerebral contusion, diffusive axonal injury) 6 months - 5 years before inclusion to this study. Authors analyzed differences in clinical symptoms of CCI in adolescents compared to previously published data for pediatric patients. CCI consequences in adolescents are prolonged; they can be accompanied with disorders of movement coordination, high psychical functions, behavior and social adaptation. Obvious disorders can be hidden in adolescents experienced CCI until they are back to school education, though they reveal decrease of ability to education. Peptidergic nootropic drug Cerebrolysin proved its effectiveness for correction of disorders of behavior, high psychical (memory, attention, controlling functions) and motor (coordination) functions, and speed of cognitive and motor operations. Key words: adolescents, craniocerebral injury, consequences, therapy, nootropic drugs, cerebrolysin. (Voprosy sovremennoi pediatrii - Current Pediatrics. - 2010;9(4):57-67)